PENGARUH PENDIDIKAN GIZI TERHADAP PENGETAHUAN DAN PRAKTIK IBU DALAM PEMBERIAN MAKAN BALITA GIZI KURANG (Studi Pada Ibu Balita Usia 12-36 Bulan di Wilayah Kerja Puskesmas Bergas Kabupaten Semarang) - novia nursetiya utomo; Sri Achadi Nugraheni; M. Zen Rahfiluddin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The nutritional problem of vulnerable toddlers is malnutrition. The impact of malnutrition can affect the growth of children under five, immune system disorders, the risk of developing infectious diseases increases and the risk of death. The influencing factor is the lack of knowledge and practice of the mother in poor feeding. Efforts to improve mothers' knowledge and practice in good feeding through nutrition education. The type of this research is Quasy Experiment Design with Non Equivalent Control Group design. The number of samples in each group is 35 people with purposive sampling technique. Each group was given a pre test and then given a home education nutrition education with a media booklet to the treatment group for 1 week, then post test for the two groups. Test for normality using Shapiro Wilk. Data analysis used Paired t-test, Wilcoxon Signed Ranks Test, Independent t-test, Mann Whitney and Chi Square. The results showed that there was an increase in knowledge of good categories by 40% and an increase in maternal practice in feeding good categories by 31.4%. Based on the Mann Whitney test there are differences in knowledge (p = 0.001), maternal practice in feeding (p = 0.005), energy sufficiency level (p = 0.002) and protein adequacy level (p = 0.001). The conclusion of this study is that there is an influence of nutrition education on increasing knowledge of the nutritional needs needed by toddlers. The suggestion from this research is that mothers should increase their knowledge about the nutritional needs of toddlers so that they can provide good practices to prevent toddlers suffering from malnutrition.Keyword : Nutrition Education, Nutritional Knowledge, Practices of Feeding, Toddlers, Poor Nutrition